THE EFFECT OF EGG YOLK LEVELS IN TRIS DILUENTS ON ABNORMALITY AND PLASMA MEMBRAN INTERGRITY OF SEMEN MUSCOVY DUCK (Cairina moschata) - HARSA, DZAKY FATIH; Rasad, Siti Darodjah; Setiawan, Iwan (Fakultas Peternakan, Universitas Padjadjaran, 2023)
Entog (Cairina moschata) is a very potential waterfowl. Attempts to increase the population by diluting semen with Tris diluent. The addition of egg yolks is necessary to avoid cold shock. The purpose of this study was to determine the effect of egg yolk in Tris diluent on abnormalities and integrity of the plasma membrane of sperm. This research was conducted in January – February 2022 at the Faculty of Animal Husbandry, Padjadjaran University. This study used a completely randomized design (CRD) method with 4 treatments and 5 replications. The treatments used were egg yolk level 5% (T1), egg yolk level 10% (T2), egg yolk level 15% (T3), and egg yolk level 20% (T4) in Tris diluent. Data were analyzed by Duncan Multiple Range Test. Based on the results it can be concluded that the addition of egg yolk levels into the Tris diluent affects the abnormality and plasma membrane integrity of sperm. The addition of egg yolk 20% in Tris diluent is the best level to preserve abnormality and plasma membrane integrity of sperm.Keywords: Tris diluent, egg yolk, muscovy duck Sperma’s, Abnormality, Plasma membrane Integrity